PERAN BUMDes DALAM PEMANFAATAN SDM DAN SDA LOKAL DESA RANTAU SAKTI - Sutriono (Jurnal Ilmiah Cano Ekonomos, 2023)
BUMDes management must prioritize the existence of regional potential or potential possessed by the village itself. Village potential is all natural resources and human resources owned by the village as basic capital that needs to be managed and developed for the survival and development of the village. This research aims to find out the role of BUMDes in realizing independent villages in Rantau Sakti Village, District North Tambusai and to find out about efforts to increase the role of BUMDes in creating an independent village in Rantau Sakti Village. Research informants were selected purposively sampling. Data collection techniques used were interviews and observation. Technique The data analysis used in this research is qualitative data analysis techniques. Research result shows that BUMDes cannot fully play a role in realizing villages independent in Rantau Sakti Village. BUMDes has played a role in improving community businesses in managing village economic potential, developing business cooperation between villages and third parties, creating opportunities and market networks that support service needs general citizens, as well as opening up employment opportunities.